The use of reverse osmosis and nanofiltration in wastewater purification from phosphates - Seminska, O.O.; Kucheruk, D.D.; Balakina, M.M.; Goncharuk, V.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The efficiency of the wastewater purification from phosphates by low pressure reverse osmosis and nanofiltration is investigated. It is shown that, for wastewater treatment, where the content of phosphate ions is less than 130 mg/dm3, it should be recommended to use the nanofiltration membrane having a high specific productivity. When the concentration of phosphate ions is from 130 to 400 mg/dm3, it is advisable that the reverse osmosis purification is carried out. At higher initial concentrations, reverse osmosis should be preceded by a process that can significantly reduce the phosphate content, such as a reagent precipitation to obtain a mineral fertilizer.